The Low Frequency Superiority Effect in Recognition Memory - Muzzin, Linda (My University, 1972)
Two explanations for the low-frequency superiority effect in recognition memory are described and a third, distractor-type hypothesis is developed. The distractor-type hypothesis proposes that Ss have a preference for abstracting semantic features from high-frequency words and acoustic features from low-frequency words. It suggests that low-frequency superiority is a result of semantic interference with high-frequency words combined with a lack of acoustic interference with low-frequency wods. The results of three experiments which support this hypothesis are required. Experiments I and II showed that more acoustic than semantic-type errors are made with low-frequency words and more semantic than acoustic-type errors are made with high-frequency words in the recognition memory paradigm. Experiments III of this series examined the relationship of the distractor type and distractor frequency variables.
Keywords: Psychology; Psychology